PROBLEMATIKA PERILAKU KONSUMEN LEMBAGA KEUANGAN DAN PERBANKAN ISLAM - Darwis Harahap; Rahmat Husein Lubis (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sumatera Utara, 2021)
This study aims to determine the problems that exist in consumer behavior in Islamic financial and banking institutions. To find out this, a research was conducted on consumer behavior especially at Islamic Banks. This study uses a qualitative approach using secondary data. The results of the analysis show that there are several consumers behavior problems related with their intention and interest towards Islamic banks namely: religious/beliefs, culture factor and social factors, personal factors, psychology, motivation, perception, learning process, attitudes, ease and speed of processing, location and physical attributes, price, employee service.